Public Health Preparedness for Global Pandemics - Joaquim Pinto; Eugenia Carvalho de Araujo; Carlos Boavida Tilman; Adelina Pinto; Manuel Fransisco da Costs (Medical Studies and Health Journal (SEHAT), 2024)
This study aims to explore the main activities involved in public health preparedness for a global pandemic. These activities include strong supervision and monitoring, comprehensive risk assessment, adequate resource allocation, comprehensive emergency response planning, global coordination, training and capacity building, effective communication and information sharing, and continuous evaluation and improvement. In addition, strategies to ensure health system flexibility are also considered, including health service infrastructure and capacity building, health system strengthening, a multi-sector approach, an all-threat approach, flexibility in infrastructure design, and effective resource allocation and mobilization. By implementing these strategies, it is hoped that health systems can increase their resilience, responsiveness and ability to meet the needs of affected populations during the global pandemic.